IDENTIFIKASI KEANEKARAGAMAN HAYATI BIOTA PERAIRAN PADA SUNGAI UTAMA DI KOTA BEKASI - Nana Danapriatna (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2005)
Variety involve is one of fundamental issue which must be solved and integrated in development, especially development of area. Therefore, it is important to know elementary information concerning variety involve territorial water ecosystem biodiversity. Target of this research is to know the quality of environment seen from variety aspect involve territorial water biota especial river in Bekasi. Result of research indicate that situation of especial river in Bekasi namely Cikeas, Cileungsi, Kali Bekasi, and Tarum BdfSt at observation of February 2004 is as following (a) Variety index of phytoplankton highest in kali Bekasi while tarum bdrdtas control still under him (b). Variety index of zooplankton highest in Kali Bekasi (c) Index Variety of benthos highest in Cikeas value ofabove I. Pursuant to variety index of benthos, hence entire/all river perceived have pertained impure of weight except Cikeas